Inhibitory effects of Cu, Zn, Ni and Co on nitrification and relevance of speciation - SEMERCİ, NESLİHAN (WILEY, 2010)
BACKGROUND: The speciation of metals is often overlooked in understanding their observed inhibitory effect in biological systems, in particular in nitrification systems. This study examines the effects of Cu, Zn, Ni and Co on a nitrifying sludge, where the aim is to relate inhibition to speciation. RESULTS: Nitrification inhibition was monitored by O-2 and CO2 measurements, an approach rarely followed to date. The IC50 value of each metal was expressed in terms of total, free and labile metal. Zn and Cu formed similar species, but had different free and labile fractions. Although free and labile fractions of Cu were much lower than the others, it was the most inhibitory metal. Ni and Co exhibited quite different inhibitory effects on nitrification despite the formation of similar metal species. Co was the least inhibitory metal and exhibited its effect very slowly. CONCLUSION: The study is among the few which examine inhibition and speciation of several metals in a comparative way. In the same nitrification medium each metal formed different species, which is a factor to be considered in interpretation of inhibition. The results may be projected to nitrifying systems to clarify the underlying factors in inhibition. (C) 2009 Society of Chemical Industry
Keywords: metal; speciation; nitrification; respirometry; inhibition; WATER TREATMENT-PLANT; CADMIUM SPECIATION; METAL SPECIATION; NICKEL